Does the design of the shelter influence the levels of behavioural stress and aggression in group-housed male guinea pigs? - Nordlund, Angelica (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
For animals, such as the guinea pig, which are obtained from breeders, it is of legal as well as of scientific concern that the animals have an acclimatization period just after arriving at their new animal facility. During this period, the guinea pigs have a chance to decrease the levels of stress, caused by the process of moving. This study aims to imporove the housing conditions of guinea pigs during the acclimatization period by evaluating if the design of shelter for hiding affects the guinea pigs' levels of behavioural stress and aggression. The present study was done at AstraZeneca R&D in Mölndal, where guinea pigs are used as an animal model in the process of developing new drugs. In the experiment 104 male guinea pigs of the Duncan Hartley strain were used, livin in groups of four. Two different shelter designs were used: one type with one entrance and one compartment callec "box for group hiding", BGH, and the second type with four entrances and four compartments called "grage for single hiding", GSH. Behavioural data was collected by video recorded and direct observations during the 1th, 2nd, 3rd, 6th and 7th day after arrival. Each day of direct observations was divided into three periods of observation, during which frequencies of 17 different behaviours were recorded. All individuals were observed for a total of about one hour. Data from video recorded observations were collected during two 3 hour periods. Data was tested using the Mann-Whitney U test, the Variance Analysis test and the Simple Linear Regression.